2002
DOI: 10.1046/j.1365-2109.2002.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effect of using the rotifer, Brachionus plicatilis , treated with different nutritional enrichment media and antibiotics on the growth and survival of blue-fin sea bream, Sparidentex hasta (Valenciennes), larvae

Abstract: Studies were carried out to determine the effect of using the rotifer, Brachionus plicatilis (Muller) (S‐type), subjected to different treatments on the growth and survival of blue‐fin sea bream, Sparidentex hasta (Valenciennes), larvae. This was to illustrate the role of mixed algae added to the oil enrichments for the treatment of the rotifers to improve the sea bream larval survival. The highest sea bream larval survival (P < 0.05) was obtained while feeding the larvae with rotifers enriched in a mixture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Taking into account that DHA levels in larvae fed prey enriched with MG were significantly higher than in those fed AG‐enriched prey, it can be suggested that DHA levels and DHA/EPA ratio influence final survival, something already observed in other species of marine fish larvae (Tocher ). In other species such as Gadus morhua (García et al ), Melanogrammus aeglefinus (García et al ), and Sparidentex until (Tawfiq Abu‐Rezq et al ), there does not seem to exist this relationship between the content of DHA in live prey and larvae and the final survival.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that DHA levels in larvae fed prey enriched with MG were significantly higher than in those fed AG‐enriched prey, it can be suggested that DHA levels and DHA/EPA ratio influence final survival, something already observed in other species of marine fish larvae (Tocher ). In other species such as Gadus morhua (García et al ), Melanogrammus aeglefinus (García et al ), and Sparidentex until (Tawfiq Abu‐Rezq et al ), there does not seem to exist this relationship between the content of DHA in live prey and larvae and the final survival.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, no significant differences (p < 0.05) in the culturable counts of heterotrophic bacteria and Vibrio spp. between untreated and oxolinic-acid-treated rotifer cultures were observed, resulting in the conclusion that antibiotic-treated rotifers used to feed reared larvae of blue-fin seabream are not needed to improve larval survival [67]. By contrast, the bacterial loads on both rotifers and Artemia were reduced with antibiotics [10], but until now, effective bacterial reduction in mass-produced rotifers remains an unsolved issue.…”
Section: Discussionmentioning
confidence: 99%
“…The requirements of common dentex larvae for dietary EPA are close to those found in fish larvae from temperate water, such as Pseudocaranx dentex (>3.1%; Takeuchi et al, ) and Limanda ferruginea (3.5%; Copeman et al, ). Common dentex EPA requirements were higher than those of the temperate species Paralichthys olivaceus (1%; Furuita et al, ) and lower than that of the warm water species Sparidentex hasta (19.3%; Abu‐Rezq et al, ).…”
Section: Resultsmentioning
confidence: 98%